2011
DOI: 10.1007/s13311-011-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Ischemic Stroke: Beyond Thrombolysis and Supportive Care

Abstract: The initial therapeutic approach to acute ischemic stroke consists of thrombolytic therapy and early initiation of supportive care, usually commenced prior to the determination of the underlying stroke etiology. Varying stroke mechanisms may call for specific, etiology-based treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
7
0
1
Order By: Relevance
“…Cervical artery dissection (CAD), either spontaneous or caused by underlying connective tissue disease or trauma, may result in thromboembolism or hemodynamic impairment [1]. It has been estimated that carotid or vertebral Electronic supplementary material The online version of this article (doi:10.1007/s00415-015-7829-x) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical artery dissection (CAD), either spontaneous or caused by underlying connective tissue disease or trauma, may result in thromboembolism or hemodynamic impairment [1]. It has been estimated that carotid or vertebral Electronic supplementary material The online version of this article (doi:10.1007/s00415-015-7829-x) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective assessment of zero-degree head positioning in the first 24 h after acute ischemic stroke showed that risk of subsequent aspiration pneumonia is less than 5% [24]. These findings have led to the recommendation of supine positioning as standard care for patients who can tolerate it [6,25,26,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Prolonged vascular injury can lead to small vessel occlusion and cerebral infarction [1]. Blood vessels in response to injury or atherosclerosis usually display intimal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic stenosis or occlusion of a major cerebral artery is a leading cause of stroke [1-3]. Several experimental models have been developed for the study of cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%